2008
DOI: 10.1152/ajpregu.00915.2007
|View full text |Cite
|
Sign up to set email alerts
|

Branchial expression patterns of claudin isoforms in Atlantic salmon during seawater acclimation and smoltification

Abstract: In euryhaline teleosts, permeability changes in gill epithelia are essential during acclimation to changed salinity. This study examined expression patterns of branchial tight junction proteins called claudins, which are important determinants of ion selectivity and general permeability in epithelia. We identified Atlantic salmon genes belonging to the claudin family by screening expressed sequence tag libraries available at NCBI, and classification was performed with the aid of maximum likelihood analysis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 34 publications
10
80
2
Order By: Relevance
“…Previous studies have associated changes in cldn-10e mRNA abundance with acclimation to seawater (SW), smoltification and elevated levels of cortisol (Tipsmark et al, 2008;Bui et al, 2010;Bui and Kelly, 2011). In an SSI preparation derived from the gills of T. nigroviridis, cldn-10e was found to be absent (Bui et al, 2010), and it was subsequently shown that in gill tissue of this species Cldn-10e localizes exclusively to mitochondria-rich cells (Bui and Kelly, 2014).…”
Section: Research Articlementioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have associated changes in cldn-10e mRNA abundance with acclimation to seawater (SW), smoltification and elevated levels of cortisol (Tipsmark et al, 2008;Bui et al, 2010;Bui and Kelly, 2011). In an SSI preparation derived from the gills of T. nigroviridis, cldn-10e was found to be absent (Bui et al, 2010), and it was subsequently shown that in gill tissue of this species Cldn-10e localizes exclusively to mitochondria-rich cells (Bui and Kelly, 2014).…”
Section: Research Articlementioning
confidence: 94%
“…cldn-1, -3a, -7, 13, -30, tric, cgn and zo-1) did not alter in abundance over the SSI culture period, despite the changes in paracellular permeability. In the case of cldn-30, this is a curious observation because Cldn-30 has been proposed to be an important determinant in the maintenance of reduced gill epithelium permeability by virtue of the fact that significant changes in mRNA abundance have previously been associated with changes in environmental salinity (Tipsmark et al, 2008;Chasiotis and Kelly, 2011a;Chasiotis and Kelly, 2012;Chasiotis et al, 2012b) and corticosteroid-induced reductions in gill epithelium permeability (Chasiotis and Kelly, 2011a;Kelly and Chasiotis, 2011). Furthermore, the absence of cldn-30d/Cldn-30d in zebrafish (known as cldn-b) has been suggested to result in an increase in diffusive Na + loss across the integument (Kwong and Perry, 2013) and Cldn-30 has been proposed to reduce cation permeability across the gill epithelium of Atlantic salmon (Engelund et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…In the euryhaline (diadromous) Atlantic salmon, it has been suggested that cldn-10e is a gill-specific claudin isoform as its transcript abundance is several orders of magnitude greater in gill tissue than tissues such as the brain, intestine, kidney and liver (Tipsmark et al, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…The following Fugu sequences (and respective accession numbers) were used in the BLAST search: claudin-3a (AY554377), claudin-7b (AY554347), claudin-8d (AY554390), claudin-12 (AY554346), claudin-31 (AY554351) and claudin-32a (AY554360). The following Atlantic salmon sequences were used in the BLAST Tipsmark et al, 2008), except for claudin-8d and claudin-32a, which were named according to Fugu terminology originally described by Loh et al (Loh et al, 2004) as salmon orthologs for these claudins have yet to been identified. Full-length and partial coding sequences for rainbow trout claudin-3a, -7, -8d, -12, -30, -31 and -32a were submitted to the Third Party Annotation (TPA) database and accession numbers are shown in Table1.…”
Section: Identification Cloning and Qrt-pcr Analysis Of Mrna Encodinmentioning
confidence: 99%